ASSESSING THE ROBUSTNESS OF A HYPERTENSION SURVEILLANCE SYSTEM: A CASE STUDY IN THE WORKING AREA OF THE DENPASAR CITY HEALTH OFFICE, 2025 - Ni Luh Rahayu Widaryati; Putu Ayu Swandewi Astuti; Putu Dwi Adi (Lux Mensana: Journal of Scientific Health, 2026)
Introduction. Hypertension is widely recognized as a silent killer and risk factors of stroke and cardiovascular disease. Within Denpasar City, the prevalence of hypertension remains notably elevated. Surveillance systems constitute an indispensable instrument for the ongoing monitoring and control of hypertension. The present study sought to evaluate the hypertension surveillance system operating within the jurisdiction of the Denpasar City Health Office during 2025. Method. A qualitative case study design was used. Data collected through in-depth interviews conducted with non-communicable disease program officers at the Denpasar City Health Office and at four community health centres (Puskesmas) selected via simple random sampling. The data analysed with descriptive analysis. Result & Analysis. The result shows that the hypertension surveillance system was operational yet fell short of optimal performance. Principal constraints were identified in the areas of limited human resource capacity, excessive dual workloads among frontline staff, and fragmented reporting mechanisms. The ASIK application was frequently subject to technical disruptions, lacked integration with the existing E-Puskesmas system and depended on staff’s personal devices. Furthermore, only a subset of community health volunteers demonstrated the capability to perform independent data input. The system performed adequately in acceptability and representativeness; however, significant deficiencies were observed in the domains of simplicity, timeliness, and stability. Conlusion. Strengthening is needed in human resource development, digital system integration, provision of adequate supporting infrastructure, and structured training programs for community health volunteers to improve system effectiveness and sustainability.